Lafora disease: A case report - Manel Yahia; Besma Laabidi; Issam M'sakni; Fethi Bougrine; Ammar Bouziani (Our Dermatology Online, 2016)
Introduction: Lafora disease is a rare and severe form of progressive myoclonus epilepsy. It is an autosomal recessive disease, genetically heterogeneous. Aim: Our aims is to study the clinic-pathological features of this rare entitie We report a case of Lafora disease. Case Report: We report the case of a 16 year old girl, which shows from the age of 14 myoclonus epilepsy. Neurological examination showed cerebellar syndrome and intellectual deterioration. Skin biopsy was needed to guide the diagnosis. The Lafora disease has a constantly fatal prognosis. Histological examination confirms the diagnosis and molecular study may help to establish a genetic counseling. Conclusion: Lafora disease has significant clinical and evolutionary characteristics that should guide the clinician to achieve axillary skin biopsy to find Lafora bodies.